Increased risk for child maltreatment in those with developmental disability: A primary health care perspective from Israel. (November 2020) - Karni-Visel, Yael; Hershkowitz, Irit; Hershkowitz, Fabienne; Flaisher, Michal; Schertz, Mitchell
Abstract: Background: Child Maltreatment (CM) is a worldwide phenomenon. Literature suggests that children with disabilities are at increased risk for CM. However, limited information exists regarding if such increased risk is noted in community primary care clinics. Aim: To report on the incidence of CM in children with and without disabilities attending community primary care clinics. Method: This was a cohort study of children belonging to a Health Maintenance Organization (HMO) in Israel. The study group consisted of children with disabilities and the control group consisted of children without disabilities. Formal reports to child protection services, medical and sociodemographic data were extracted from designated documentation and medical records. Results: The odds to be identified as suspected CM, after adjusting for sociodemographic variables, was 6.2 times higher among children with disabilities compared to children without disabilities and 5.0 times higher among children with severe vs. mild disability. Conclusions: Developmental disability is a risk factor for CM, and is noted even more seriously in community primary care clinics. CM positively correlated with the severity of disability. The presented data marks higher figures than previously reported, enhancing understanding of the scope of the problem and its relation to the type of organization being examined.